Preexisting epithelial diversity in normal human livers: A tissue‐tethered cytometric analysis in portal/periportal epithelial cells12. Issue 4 (19th March 2013) - Isse, Kumiko; Lesniak, Andrew; Grama, Kedar; Maier, John; Specht, Susan; Castillo‐Rama, Marcela; Lunz, John; Roysam, Badrinath; Michalopoulos, George; Demetris, Anthony J.
Abstract Routine light microscopy identifies two distinct epithelial cell populations in normal human livers: hepatocytes and biliary epithelial cells (BECs). Considerable epithelial diversity, however, arises during disease states when a variety of hepatocyte‐BEC hybrid cells appear. This has been attributed to activation and differentiation of putative hepatic progenitor cells (HPC) residing in the canals of Hering and/or metaplasia of preexisting mature epithelial cells. A novel analytic approach consisting of multiplex labeling, high‐resolution whole‐slide imaging (WSI), and automated image analysis was used to determine if more complex epithelial cell phenotypes preexist in normal adult human livers, which might provide an alternative explanation for disease‐induced epithelial diversity. "Virtually digested" WSI enabled quantitative cytometric analyses of individual cells displayed in a variety of formats (e.g., scatterplots) while still tethered to the WSI and tissue structure. We employed biomarkers specifically associated with mature epithelial forms (HNF4α for hepatocytes, CK19 and HNF1β for BEC) and explored for the presence of cells with hybrid biomarker phenotypes. The results showed abundant hybrid cells in portal bile duct BEC, canals of Hering, and immediate periportal hepatocytes. These bipotential cells likely serve as a reservoir for the epithelial diversity of ductular reactions, appearance of hepatocytes in bile ducts, and the rapid and fluid transition of BEC to hepatocytes, and vice versa. Conclusion: Novel imaging and computational tools enable increased information extraction from tissue samples and quantify the considerable preexistent hybrid epithelial diversity in normal human liver. This computationally enabled tissue analysis approach offers much broader potential beyond the results presented here. (HEPATOLOGY 2013)